The Oxford handbook of dialectical behaviour therapy - Swales, Michaela A. (Oxford library of psychology, 2017)
This handbook examines theoretical, structural, clinical and implementation aspects of dialectical behaviour therapy (DBT) for a variety of disorders such as borderline personality disorder (BPD), suicidal behaviour in the context of BPD, substance use disorders, cognitive disabilities, eating disorders, and post-traumatic stress disorder (PTSD). The volume considers the dialectical dilemmas of implementation with respect to DBT in both national and international systems, its adaptations in routine clinical settings, and its behavioural foundations. It also discusses evidence-based training in DBT, validation principles and practices in DBT, the biosocial theory of BPD, the structure of DBT programs, and the efficacy of DBT in college counseling centers.